2000
DOI: 10.1001/archpedi.154.8.763
|View full text |Cite
|
Sign up to set email alerts
|

The Cost-effectiveness of Adolescent Hepatitis A Vaccination in States With the Highest Disease Rates

Abstract: Hepatitis A vaccination of adolescents in states with high disease rates would reduce costs to society. Although health system costs would increase, cost-effectiveness is comparable to other recommended vaccines and superior to many commonly used medical interventions. Arch Pediatr Adolesc Med. 2000;154:763-770

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 42 publications
(57 reference statements)
0
57
0
3
Order By: Relevance
“…The same panel calls for studies exploring long-term protection after a single dose, concluding it is currently not established (52). Our reference case assumptions regarding duration of protection are based on another expert panel's opinion (42). Because these estimates are speculative, sensitivity analyses were conducted with wide variation in reference case assumptions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same panel calls for studies exploring long-term protection after a single dose, concluding it is currently not established (52). Our reference case assumptions regarding duration of protection are based on another expert panel's opinion (42). Because these estimates are speculative, sensitivity analyses were conducted with wide variation in reference case assumptions.…”
Section: Discussionmentioning
confidence: 99%
“…The probabilities of receiving the first and second doses were assumed to be independent, leading to the coverage estimates reported in Table 3. For the reference case, 98% of children were assumed to develop immunity with one dose (41), but 1.62% were predicted to lose protection during each of years 1 through 10, and 2.67% were predicted to lose protection annually thereafter (42). Assumptions for two doses were that 99% of children would develop immunity (41), but 0.31% would lose protection during each of years 1 through 10, and 0.62% would lose protection annually thereafter (42).…”
Section: Immunization Coverage and Protective Efficacymentioning
confidence: 99%
“…30 In fact, taking into account a 1:1 secondary attack rate would approximately double the benefits of vaccination. 31 Current ACIP recommendations call for routine vaccination of children living in areas where hepatitis A rates are at least twice the national average. 7,19 These include 11 western states (Arizona, Alaska, Oregon, New Mexico, Utah, Washington, Oklahoma, South Dakota, Idaho, Nevada, and California) with annual rates of 20 to 48 per 100,000 between 1987 and 1997.…”
Section: Economic Analyses Of Hepatitis a Vaccinationmentioning
confidence: 99%
“…19 A recent study confirmed that vaccination in 15-year-old residents of the 10 states with the highest incidence of infection would be cost-effective by generally accepted standards. 31 A decision model that examined the risks and outcomes of hepatitis infection with and without routine vaccination of adolescents showed that the $30.9 million for vaccination would be more than offset by savings of $14.2 million in treatment costs and $23.8 million in indirect (work loss) costs resulting from reductions in the lifetime risk of symptomatic infection. 31 The cost-effectiveness ratio was calculated as $13,722 per YOLS.…”
Section: Economic Analyses Of Hepatitis a Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation